Work, culture, and play in the neoliberal condition. Issue 9 (2nd September 2018) - Elliott, Brian
ABSTRACT: Foucault's [2008. The birth of biopolitics: Lectures at the collège de France 1978–1979 . New York, NY: Picador] lectures on neoliberalism present a powerful challenge to the Marxist critique of capitalist work as alienating and dehumanizing. Foucault suggests that neoliberalism allows work to be seen in terms of an individual's pursuit of personal happiness. Seminal cultural theory in Hoggart [1957/2009. The uses of literary: Aspects of working-class life . London: Penguin] and Williams [1961. The long revolution . London: Chatto & Windus] view working-class culture as a matter of tacit rules and a 'structure of feeling' that permeates everyday life. Adorno's critique of the capitalist 'culture industry', by contrast, suggests that a culture of neoliberal capitalism would be an oxymoron. This perspective is self-defeating, I argue, as we then essentially give up the task of understanding how neoliberalism translated into a pervasive social psychology. Following Richard Sennett's [2008. The craftsman . New Haven, CT: Yale University Press; 2012. Together . New Haven, CT: Yale University Press] work on craft and cooperation, I examine some elements of such neoliberal culture. Across many contemporary cities, there is a clear trend of local small-scale production that stands at odds with the aesthetics if not the underlying reality of the globalized economy. This suggests that utopian counter-currents to neoliberal governance are better drawn from reconfiguration rather than abandonment of work.